2017
DOI: 10.1186/s13063-017-2046-9
|View full text |Cite
|
Sign up to set email alerts
|

Practical issues regarding implementing a randomized clinical trial in a homeless population: strategies and lessons learned

Abstract: There is a critical need for objective data to guide effective health promotion and care for homeless populations. However, many investigators exclude homeless populations from clinical trials due to practical concerns about conducting research with this population. This report is based on our experience and lessons learned while conducting two large NIH-funded randomized controlled trials targeting smoking cessation among persons who are homeless. The current report also addresses challenges when conducting c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 23 publications
(19 citation statements)
references
References 41 publications
(49 reference statements)
0
19
0
Order By: Relevance
“…Many factors affect the higher mortality rates among homeless adults: increased risk for mental illness, trauma, suicide, and medical comorbidities, as well as excessive alcohol and substance use. Approximately 33% of adults who are homeless suffer from some form of severe and persistent mental illness (41).…”
Section: Sexual and Gender Minority Groups: Stigma Experienced Within Mental Health Servicesmentioning
confidence: 99%
“…Many factors affect the higher mortality rates among homeless adults: increased risk for mental illness, trauma, suicide, and medical comorbidities, as well as excessive alcohol and substance use. Approximately 33% of adults who are homeless suffer from some form of severe and persistent mental illness (41).…”
Section: Sexual and Gender Minority Groups: Stigma Experienced Within Mental Health Servicesmentioning
confidence: 99%
“…A full explanation of the design and methods can be found elsewhere. (34,35) During the RCT consent process, PTQ2 participants were informed that they might be invited to participate in an interview portion of the study. Research study staff approached potential participants just prior to the nal study visit (week 26).…”
Section: Methodsmentioning
confidence: 99%
“…Power to Quit 2 (PTQ2) was a randomized controlled trial, built on the ndings from the rst PTQ study, aimed to investigate concurrent smoking cessation and alcohol treatment among people experiencing homelessness. (34,35) In this study, we present ndings from semi-structured interviews with participants completing PTQ2, where the experience of participating in a smoking and alcohol intervention were explored in order to provide insight into the challenges faced by participants when trying to quit smoking. Additionally, the analysis drew on the CFIR framework (14) to inform future learning on the intervention implementation process.…”
Section: Introductionmentioning
confidence: 99%
“…The major strength of this study is the sample of patients, who are very often excluded from research 22 and thus provide unique insight into the nature of exclusion. Trying to capture the experience and insights of both staff and patients adds an interesting and valuable dimension to the research, which has not been shown before.…”
Section: Strengths and Limitationsmentioning
confidence: 99%